Newton loop-node analysis study on gas pipeline network - Nur Syazana, Hamzah (2010)
The gas network consists of tree type network and loop type network. There are three types of network analysis, Newton Nodal Method, Newton Loop Method and Newton Loop-Node Method. This research covers on the Newton Loop-Node method. Furthermore, there are many numerical methods that can be used in performing gas network analysis. The hypothesis is Gauss Elimination is more accurate and less iteration number than Gauss Seidel. The objectives of this research are to study on the pressure and flowrate at nodes and pipeline, to determine the suitable flow equation and to compare the iteration number between Gauss Elimination and Gauss Seidel. This research focuses more on on the steady state low pressure compressible fluid and piping route in Gebeng Industrial Area. The analysis involves 5 nodes low pressure gas pipeline network. Lastly, the manual calculation of the network analysis is compare with Fortran 90 program.